Colliders And Neutrinos The Window Into Physics Beyond The Standard Model (Tasi 2006) - Dawson, Sally; Mohapatra, Rabindra N (World Scientific Publishing Company, 2008)
This book is a collection of theoretical advanced summer institute lectures by world experts in the field of collider physics and neutrinos, the two frontier areas of particle physics today. It is aimed at graduate students and beginning researchers, and as such, provides many pedagogical details not generally available in standard conference proceedings.